(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Knowledge management is the process of defining, structuring, retaining and sharing the knowledge and experience of employees within an organization. The objective of knowledge management is improving an organization’s efficiency and save knowledge within the company. e-Governance is the application of Information and Communication Technology (ICT) at all the level of the Government for providing services to the citizens, interaction with business enterprises and communication and exchange of information among different agencies of the Government in a speedy, convenient efficient and transparent manner.